PERANAN PENDEKATAN PLAY-BASED LEARNING DALAM MENINGKATKAN MINAT TERHADAP STEAM - Hasdiana, Hasdiana; Ulin Naini (Prosiding Seminar Nasional Indonesia, 2025)
This study aims to examine the role of play-based learning in increasing children's interest in STEAM (Science, Technology, Engineering, Art, and Mathematics) through a literature review method. The results of the literature review show that play-based learning can create an active, enjoyable, and meaningful learning environment, making it easier for children to engage and be motivated to explore STEAM concepts. This approach also encourages the development of creativity, critical thinking skills, as well as collaboration and communication skills in children. Additionally, play-based learning provides children with the opportunity to experiment, innovate, and learn from direct experiences, ultimately fostering their interest and passion for STEAM fields. Therefore, the implementation of play-based learning is highly recommended in STEAM education to support the development of children's interests and competencies in the era of globalisation and technological advancement.